2005
DOI: 10.1111/j.1365-2745.2005.01087.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved resolution of pollen taxonomy allows better biogeographical interpretation of post‐glacial forest development: analyses from the North American Pollen Database

Abstract: Summary1 Species-level pollen identifications within the genera Acer , Fraxinus and Juglans have the potential to increase the detail available from regional-and landscape-scale studies of palaeo-forest dynamics. 2 Data from the North American Pollen Database (NAPD) and the North American Modern Pollen Database (NAMPD) for sites in eastern North America for which species-level identifications have been recorded enabled us to consider pollen taxonomy at high resolution. 3 Species within each of Acer , Fraxinus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…Birks (1994) concluded that the transfer functions performed best if all taxa were included unless WA was calculated with tolerance down-weighting. In a second study, Finkelstein et al (2006) indicated that species-level identification of fossil pollen allowed more complete reconstruction of the vegetation history of eastern North America than records identified to genus-level.…”
Section: Discussionmentioning
confidence: 99%
“…Birks (1994) concluded that the transfer functions performed best if all taxa were included unless WA was calculated with tolerance down-weighting. In a second study, Finkelstein et al (2006) indicated that species-level identification of fossil pollen allowed more complete reconstruction of the vegetation history of eastern North America than records identified to genus-level.…”
Section: Discussionmentioning
confidence: 99%
“…Within the vast literature about calibration data-sets, some papers critically identify and discuss in detail some of these potential errors (e.g. Birks et al 1990;Jones & Juggins 1995;Lotter et al 1997Lotter et al , 1998Engels et al 2001Engels et al , 2008Bigler et al 2002;Whitmore et al 2005;Finkelstein et al 2006;Heiri et al 2007;Gonzales et al 2009a;.…”
mentioning
confidence: 99%
“…and associated climate data (X m ) is available. This data-set should be representative of the likely range of climate variables in the past (X f ), be of consistent and detailed taxonomy and nomenclature (Finkelstein et al 2006), be of comparable quality (data-extraction procedures, spatial scale, count size, sampling methodology, preparation procedures, counting techniques) and, in the case of surface samples, be from the same type of sedimentary environment as the fossil samples (e.g. lakes) (Bjune et al 2010) and hence have comparable taphonomies (cf.…”
mentioning
confidence: 99%
“…Taxonomic resolution is also important in biogeographical studies. For example, identification of pollen down to species level can reveal shifts in plant assemblages that are not apparent with lower resolution (Finkelstein et al 2006). In studies of environmental impact assessment, including many investigations of the impacts of pollution on aquatic habitats, low levels of taxonomic resolution can obscure important changes to the biota (Terlizzi et al 2003(Terlizzi et al , 2009Jones, 2008).…”
Section: Discussionmentioning
confidence: 99%